The Effects of Avocado Waste and Its Functional Compounds in Animal Models on Dyslipidemia Parameters - Pineda-Lozano, Jessica Elizabeth; Martínez-Moreno, Alma Gabriela; Virgen-Carrillo, Carmen Alejandrina (Frontiers in Nutrition, 2021)
Ischemic heart disease and stroke are the two main causes that have prevailed for more than 15 years. Dyslipidemia and its parameters like hypercholesterolemia, hypertriglyceridemia, increase in low density cholesterol and a reduction of high-density cholesterol have been related with heart disease and risk of stroke. Approaches to improve the health and specifically reduce the risk of heart disease, such as medications and dietary interventions have been effective, but there is another potential source of biological compounds that can made a potential effect due to its antioxidant effect. Avocado is a commonly consumed fruit especially by its pulp; while the peel, seed and leaf are usually discarded as waste. Some researchers have reported antioxidant, hepatoprotective, gastroprotective, lipid-lowering and hypoglycemic effects by these wastes. In this review article, we have summarized the current evidence on the effect of biological compounds from avocado waste on dyslipidemia parameters in preclinical models. Also, we have included the compound extracted and the extraction method from the selected articles.